Acceleration Model for Economic Development in Disadvantaged Regions of East Java Province - Mohammad Wahed; Sishidiyati Sishidiyati; Agung Winarno (Budapest International Research and Critics University, 2022)
The aim of this study is to determine the reasons for poverty and to identify priority development plans for East Java's disadvantaged regions (Sampang, Bangkalan, Situbondo, and Bondowoso). The Analytical Hierarchical Process (AHP) approach is used to analyze secondary and primary data in this study. The poverty rate in East Java's four disadvantaged areas (Bondowoso, Situbondo, Bangkalan, and Sampang) is relatively much higher than the national average, and Sampang Regency has the highest rate among the three disadvantaged regions. The high prevalence of poverty in disadvantaged regions is a result of economic (income, nutrition, and housing) and social issues (alienation, feeling insecure), as well as politics and culture (Moeis, 2006). Regional development policy priorities aimed at boosting economic growth in four disadvantaged regions (Sampang, Bangkalan, Bondowoso, and Situbondo), namely: 1) Strengthening Microeconomics; 2) Optimizing Resources; 3) Improving Institutional Performance; 4) Developing Tourism Potential.